Perencanaan Struktur Gedung Kantor (DPMPTSP, Disnaker, Diskes dan Capil) Kabupaten Gianyar dengan Menggunakan Flat Slab - Mulia, Hendy Ardhito; Triswandana, I Wayan Gde Erick; Aryastana, Putu; Sarassantika, I Putu Ellsa (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
In the construction, it must be able to be used according to its function so that it can be used for a long time. The concept of construction that has sufficient strength and allows for large spaces without affecting aesthetics has emerged in recent decades. A flat slab is one of the advances in the construction system of a two-way concrete plate that distributes the working load directly to the column element without using a beam. The use of drop panels can increase the strength of the plate by resisting the sliding style of the pons and reducing the negative moment reaction that occurs on the plate and column. In the analysis, the results used a flat slab with a thickness of 200 mm, with bones in the x and y directions at the focus of As D16-100 mm and As’ D16-200 mm, whereas in the columns of column directions x and y, the field part is mounted with As D13-100 mm and As‘ D13-200 mm. In the middle column of directions X and Y, use the bones of As D13-100 mm and As‘ D13200 mm. Used a drop panel of 300 mm. For the lift area, an L type column with dimensions of 450 mm x 450 mm is used. The bars used are TB1, TB2, B1, and RB, and the columns used are 500 mm x 500 mm and 400 mm x 400 mm. The planned foundation uses a cylinder-shaped pillar with a depth of up to 8 meters.